CuCr-X alloy, preparation method and application thereof
By adding Sn, Mg, and Ti elements to the CuCr-X alloy and using specific process treatments, a small precipitation phase was formed, which solved the problem of insufficient stress relaxation performance in high-temperature environments, and achieved good strength, conductivity and stress relaxation performance.
Patent Information
- Application Number
- CN202411616628.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-13
AI Technical Summary
The existing CuCr-X alloys have insufficient stress relaxation resistance under high temperature environments, which affects the reliability of electronic devices.
By optimizing the alloy composition, the specific content of Sn, Mg, and Ti elements are increased, and multi-pass cold rolling, recrystallization and over-age treatment are used to form a small and evenly distributed precipitation phase to improve the stress relaxation resistance of the alloy.
The tensile strength, conductivity and stress relaxation resistance of CuCr-X alloy are significantly improved, and the stress relaxation rate after 1000 hours can be maintained at a temperature of 150°C at a temperature of 150°C, meeting the needs of high-end connectors in high-temperature and high-vibration environments.
Smart Images

Figure CN119120981B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nonferrous metal processing, and in particular to a CuCr-X alloy, a preparation method and application thereof. Background Art
[0002] In recent years, with the rapid development of new energy vehicles and aerospace, the improvement of intelligence and automation, the integration of electronic circuits has increased, and the demand for connectors has also increased significantly. At the same time, the requirements for large vibration and high temperature application environments in these fields have also increased the requirements for connector reliability. Therefore, the shrapnel material used in connectors must have high stress relaxation resistance.
[0003] Traditional beryllium copper, titanium bronze and high-tin phosphor bronze alloys have some shortcomings, such as low material conductivity or insufficient stress relaxation resistance. Especially when the ambient temperature rises to 150°C or above, the stress relaxation resistance of these materials will drop rapidly, seriously affecting the operating reliability of electronic devices.
[0004] CuCr-X alloys are typical aging precipitation strengthened high-strength and high-conductivity alloys. Their finished strips have a strength greater than 550MPa and a conductivity greater than 75%IACS, and their heat resistance can reach above 500°C, fully meeting the current high-end connectors' requirements for strength, conductivity and heat resistance. However, compared with beryllium copper and titanium bronze, the stress relaxation resistance of conventional CuCr-X alloys still has a certain gap and needs further improvement. JP6283048B2 provides a copper alloy containing Cr, Ti, and Si elements, but its stress relaxation resistance is still insufficient. Summary of the invention
[0005] The main purpose of the present invention is to provide a CuCr-X alloy, a preparation method and application thereof, so as to solve the problem of poor matching of strength, electrical conductivity and stress relaxation resistance of CuCr-X alloy in the prior art.
[0006] In order to achieve the above object, according to one aspect of the present invention, a CuCr-X alloy is provided. The composition of the CuCr-X alloy includes, by weight percentage, 0.7-1.5% Cr, 0.05-0.4% Sn, 0.02-0.4% Mg, 0.02-0.2% Ti, and the balance is Cu and unavoidable impurity elements, wherein Cr / (Mg+Ti)=3-6.
[0007] Furthermore, the composition of the CuCr-X alloy includes, by weight percentage, 0.85-1.25% Cr, 0.15-0.28% Sn, 0.11-0.2% Mg, 0.05-0.15% Ti, and the balance is Cu and unavoidable impurity elements, wherein Cr / (Mg+Ti)=4-5.
[0008] Furthermore, in the composition of the CuCr-X alloy, the total weight percentage of Sn and Mg is 0.2-0.5%.
[0009] Furthermore, in the composition of the CuCr-X alloy, the total weight percentage of Sn and Mg is 0.3-0.4%.
[0010] Furthermore, the tensile strength of the CuCr-X alloy is 580-650 MPa, the electrical conductivity is 75-82% IACS, and the stress relaxation rate after being maintained at 150° C. for 1000 hours is ≤8%; and / or the elongation of the CuCr-X alloy is 3-8%.
[0011] According to another aspect of the present invention, a method for preparing the above-mentioned CuCr-X alloy is provided, comprising the following steps: step S1, according to the composition ratio of the CuCr-X alloy, batching, melting and casting, and hot rolling are carried out in sequence to obtain a hot-rolled slab; the hot-rolled slab is subjected to a first cold rolling and a recrystallization treatment in sequence to obtain a strip; step S2, the strip is subjected to a second cold rolling and an overaging treatment in sequence to obtain a plate strip; step S3, the plate strip is subjected to a third cold rolling and a stress relief treatment in sequence to obtain a CuCr-X alloy.
[0012] Further, in step S1, the deformation of the first cold rolling is 75-95%; and / or, the temperature of the recrystallization treatment is 900-960°C, and the time is 1-10 min; and / or, in step S2, the deformation of the second cold rolling is 55-85%; and / or, the temperature of the overaging treatment is 450-600°C, and the time is 2-8 h; and / or, in step S3, the deformation of the third cold rolling is 40-60%; and / or, the temperature of the stress relief treatment is 300-450°C, and the time is 30-120 s; and / or, the thickness of the CuCr-X alloy is 0.05-0.5 mm.
[0013] Furthermore, in step S1, the hot rolling is performed 1 to 2 times, the starting rolling temperature is 850 to 1000°C, and the finishing rolling temperature is 650 to 800°C.
[0014] Furthermore, in step S1, the deformation amount of the first cold rolling is 80-90%; and / or the temperature of the recrystallization treatment is 920-950° C., and the time is 1-10 min.
[0015] Furthermore, in step S2, the deformation amount of the second cold rolling is 60-80%; and / or the temperature of the aging treatment is 450-550°C, and the time is 4-8 hours.
[0016] Further, in step S3, the deformation amount of the third cold rolling is 40-50%; and / or the temperature of the stress relief treatment is 300-400° C., and the time is 60-90 s.
[0017] Furthermore, in step S1, the average grain diameter of the strip is 40-90 μm.
[0018] Furthermore, in step S2, the length of the precipitated phase in the plate is 200-600 nm, and the phase distribution density is 500-1000 / μm. 2 .
[0019] Furthermore, the average grain diameter of the CuCr-X alloy is 30-60 μm.
[0020] According to another aspect of the present invention, there is provided application of the CuCr-X alloy in the automotive, aviation and aerospace fields.
[0021] The present invention optimizes the alloy composition, adds specific contents of Sn, Mg, and Ti alloying elements on the basis of CuCr alloy, and Sn, Mg, Ti and Cu cooperate with each other, can effectively eliminate matrix vacancies, reduce the creep of atoms at high temperatures, thereby helping to improve the strength and stress relaxation resistance of the alloy. Moreover, the addition of specific contents of Sn, Mg, and Ti has little effect on the electrical conductivity of the alloy. The alloy of the present invention has good strength, electrical conductivity, and stress relaxation resistance. When used in the automotive, aviation, and aerospace fields, it can meet the use requirements of high-end connectors in high temperature and high vibration environments, and ensure the reliable operation of electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0023] Figure 1 shows the grain structure diagram of the CuCr-X alloy of Example 1 of the present invention; and
[0024] Figure 2 The grain structure diagram of the CuCr-X alloy of Comparative Example 2 of the present invention is shown. DETAILED DESCRIPTION
[0025] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0026] Terminology explanation:
[0027] IACS: International Annealed Copper Standard, used to characterize the electrical conductivity of a metal or alloy (relative to standard annealed pure copper). The electrical conductivity of standard annealed pure copper is generally defined as 100% IACS.
[0028] Unless otherwise specified, the contents mentioned below are percentages by weight.
[0029] As described in the background of the present invention, the existing technology has the problem of poor matching of strength, electrical conductivity and stress relaxation resistance of CuCr-X alloy. In order to solve the above problems, in a typical embodiment of the present invention, a CuCr-X alloy is provided. In terms of weight percentage, the composition of the CuCr-X alloy includes: 0.7~1.5% Cr, 0.05~0.4% Sn, 0.02~0.4% Mg, 0.02~0.2% Ti, and the balance is Cu and unavoidable impurity elements, wherein Cr / (Mg+Ti)=3~6.
[0030] In the composition of the CuCr-X alloy of the present invention, the Cr content is 0.7-1.5%. Within this range, the strengthening effect of chromium is obvious, and the precipitation strengthening effect is particularly significant, which can greatly improve the strength and hardness of the alloy. The CuCr-X alloy with this Cr content can obtain uniformly distributed and fine Cr phase particles in the subsequent aging treatment, which is beneficial to improve the ductility of the alloy. In addition, the chromium within this range has little effect on the electrical conductivity of the alloy.
[0031] The inventors added Sn and Mg to the CuCr-X alloy. Sn and Mg can cause lattice distortion in the Cu matrix through the solid solution strengthening mechanism, effectively hinder dislocation movement, eliminate matrix vacancies, and reduce the creep of atoms at high temperatures, thereby effectively improving the strength, hardness, and ductility of the alloy, as well as improving the alloy's stress relaxation resistance. In addition, the addition of Mg is also beneficial to improving the alloy's heat resistance, so that the alloy still maintains good mechanical properties in a high temperature environment. The present invention specifically limits the content of Sn to 0.05~0.4%, and the content of Mg to 0.02~0.4%. Within this range, the strength, hardness, stress relaxation resistance and heat resistance of the alloy can be significantly improved, and the electrical conductivity of the alloy is less affected.
[0032] The composition of the CuCr-X alloy of the present invention also includes 0.02-0.2% Ti, and this content of Ti can form fine precipitate phases (such as TiCr) with copper and chromium, and the precipitate phases are evenly distributed in the matrix, which is beneficial to enhancing the strength, hardness and stress relaxation resistance of the alloy. However, if the content of Ti is too much, it may lead to excessive dissolution of Ti, excessive precipitation phases, increased lattice distortion, and reduced carrier movement speed, which may further lead to a decrease in the conductivity of the alloy. If the content of Ti is too little, it is not conducive to effectively improving the strength, hardness and stress relaxation resistance of the alloy.
[0033] The alloy composition of the present invention specifically adds Mg and Ti elements to adjust the Cr phase morphology in the CuCr alloy. After a lot of experimental work, the inventor found that when the Cr content is 0.7-1.5wt%, and Cr / (Mg+Ti)=3-6, a rod-shaped precipitate phase with a length of 200-600nm can be formed in the matrix, and the distribution density ρ of the precipitate phase is between 500-1000 / μm. 2 The precipitated phase under the above conditions can effectively hinder the expansion of dislocations, thereby helping to improve the stress relaxation resistance and ductility of the alloy. In addition, under the above conditions, the strength, electrical conductivity and stress relaxation resistance of the alloy are all good.
[0034] In summary, the present invention optimizes the alloy composition and adds Sn, Mg, and Ti alloying elements on the basis of CuCr alloy. Since the radius difference between Sn, Mg, Ti and Cu atoms is large, they are dispersed in the matrix and can produce a significant hindering effect on the movement of dislocations, thereby effectively improving the strength and stress relaxation resistance of the alloy. Among them, the Sn and Mg elements are solid-dissolved in the matrix, which can effectively eliminate matrix vacancies and reduce the creep of atoms at high temperatures, thereby helping to improve the stress relaxation resistance of the alloy. In addition, the addition of specific contents of Sn, Mg, and Ti has little effect on the electrical conductivity of the alloy, so that the alloy of the present invention can take into account strength, electrical conductivity, and stress relaxation resistance.
[0035] In order to further improve the strength and stress relaxation resistance of the alloy, in a preferred embodiment, the composition of the CuCr-X alloy includes, by weight percentage: 0.85-1.25% Cr, 0.15-0.28% Sn, 0.11-0.2% Mg, 0.05-0.15% Ti, the balance is Cu and unavoidable impurity elements, where Cr / (Mg+Ti)=4-5. Among them, the Cr content is 0.85-1.25%, which exceeds the maximum solid solubility of the alloy. During the processing (such as casting and aging precipitation process), two different scale precipitation phases (such as pure Cr phase and TiCr phase) can be formed, which is more conducive to improving the strength and stress relaxation resistance of the alloy. The alloy composition includes 0.15-0.28% Sn, 0.11-0.2% Mg and 0.05-0.15% Ti, and the improvement effect of strength and stress relaxation resistance is more obvious, and the electrical conductivity of the alloy is less affected.
[0036] In a preferred embodiment, the total weight percentage of Sn and Mg in the composition of the CuCr-X alloy is 0.2-0.5%. Under the above conditions, the strength and stress relaxation resistance of the alloy can be more effectively improved, and the electrical conductivity of the alloy is less affected.
[0037] Based on similar reasons, in a preferred embodiment, in the composition of the CuCr-X alloy, the total weight percentage of Sn and Mg is 0.3-0.4%.
[0038] In a preferred embodiment, the tensile strength of the CuCr-X alloy is 580-650 MPa, the electrical conductivity is 75-82% IACS, and the stress relaxation rate after being kept at 150° C. for 1000 hours is ≤8%; and / or the elongation of the CuCr-X alloy is 3-8%. The CuCr-X alloy of the present invention has good strength, electrical conductivity, stress relaxation resistance, and elongation.
[0039] In another typical embodiment of the present invention, a preparation method of a CuCr-X alloy is provided, comprising the following steps: step S1, according to the composition ratio of the CuCr-X alloy, batching, melting and casting, and hot rolling are performed in sequence to obtain a hot-rolled slab; the hot-rolled slab is subjected to a first cold rolling and a recrystallization treatment in sequence to obtain a strip; step S2, the strip is subjected to a second cold rolling and an overaging treatment in sequence to obtain a plate and strip; step S3, the plate and strip are subjected to a third cold rolling and a stress relief treatment in sequence to obtain a CuCr-X alloy.
[0040] In the preparation method of the present invention, the hot-rolled slab is first cold-rolled to deform the grains (for example, to deform the grains into fibers), and then recrystallization treatment is performed to adjust the grain structure and refine the grains. Cold rolling deformation is continued to accumulate deformation energy storage and store power for subsequent deformation. After aging treatment, the size and surface distribution density of the precipitated phase can be effectively adjusted to form a fine and dispersed precipitated phase. Then the third cold rolling is performed to accurately determine the thickness of the finished strip and reduce the deviation. Finally, stress relief treatment is performed to eliminate the residual stress and dislocation generated during the deformation process to obtain the final alloy product.
[0041] In the preparation method of the present invention, the processes of cold rolling, recrystallization treatment, overaging treatment, stress relief treatment and the like work in coordination with each other, which can effectively control the size of grains and precipitated phases, reduce grain boundary mobility, eliminate residual stress, and hinder the activation of movable dislocations, thereby significantly improving the strength and stress relaxation resistance of the alloy while reducing the influence on electrical conductivity.
[0042] In a preferred embodiment, in step S1, the deformation of the first cold rolling is 75-95%; and / or, the temperature of the recrystallization treatment is 900-960°C, and the time is 1-10 min. Controlling the deformation of the first cold rolling process and the time and temperature of the recrystallization treatment within the above-mentioned specific range can make the alloy more comprehensive and rapid recrystallization during the recrystallization treatment, and can also effectively adjust the size and uniformity of the grains. If the deformation of the first cold rolling is too low, it may not provide sufficient deformation energy storage for aging precipitation, which will lead to a lower precipitation phase rate, affecting the strength, electrical conductivity and stress relaxation resistance of the alloy. In addition, it will also lead to a long subsequent heat treatment time, high temperature, and increased energy consumption; if the deformation of the first cold rolling is too high, the grain size may be too large, thereby reducing the stress relaxation resistance of the alloy, and may also cause the strip to be too thin, and the final alloy size does not meet the actual requirements. In addition, if the temperature of the recrystallization treatment is too low or the time is too short, the recrystallization process may be insufficient, and the precipitated phase may not be fully dissolved, which is not conducive to the formation of a rod-shaped precipitated phase of 200~600nm; if the temperature of the recrystallization treatment is too high or the time is too long, the grain size may be too large, which is not conducive to improving the strength and stress relaxation resistance of the alloy.
[0043] In a preferred embodiment, in step S2, the deformation of the second cold rolling is 55-85%; and / or, the temperature of the overaging treatment is 450-600°C, and the time is 2-8h. Controlling the deformation of the second cold rolling process and the temperature and time of the overaging treatment within the above-mentioned specific range can make the precipitate phase precipitate more fully, which is more conducive to controlling the size and surface distribution density of the precipitate phase. If the deformation of the second cold rolling is too low, the alloy conductivity may be reduced due to insufficient precipitation power and insufficient precipitation; if the deformation of the second cold rolling is too high, the difficulty of cold deformation will increase and the alloy plate shape will be affected. If the temperature of the overaging treatment is too high or the time is too long, the grains may be too large, the precipitate phase will be coarsened, and the strengthening phase in the alloy will be excessively aggregated or dissolved, thereby affecting the stress relaxation resistance of the alloy; if the temperature of the overaging treatment is too low or the time is too short, the solute atoms in the alloy may not be fully precipitated, which is not conducive to the formation of fine and large precipitate phases, thereby affecting the strength of the alloy.
[0044] In a preferred embodiment, in step S3, the deformation of the third cold rolling is 40-60%; and / or, the temperature of the stress relief treatment is 300-450°C, and the time is 30-120s; and / or, the thickness of the alloy is 0.05-0.5mm. The deformation of the third cold rolling directly affects the thickness of the alloy product. After debugging, the inventor optimized the deformation of the third cold rolling. Under this range of deformation, the thickness of the finished strip can be more accurately controlled, the accuracy can be improved, it can meet the standard requirements, and the material consumption can be reduced. If the temperature of the stress relief treatment is too high or the time is too long, the solid solution or conductive phase may precipitate or change, resulting in a decrease in the strength, conductivity and stress relaxation resistance of the alloy; if the temperature of the stress relief treatment is too low or the time is too short, the residual stress and dislocation generated during the deformation process may not be fully removed, affecting the hardness, strength, conductivity and stress relaxation resistance of the alloy.
[0045] In addition, the aging treatment and stress relief treatment with specific parameters of the present invention cooperate with each other, which can more effectively eliminate the residual stress of cold deformation and a large number of movable dislocations in the matrix, and is more conducive to making the alloy in a stable state at high temperature, thereby further improving the alloy's stress relaxation resistance and heat resistance.
[0046] For the purpose of further improving the distribution size and density of the precipitated phase, in a preferred embodiment, in step S1, the hot rolling passes are 1 to 2 passes, the starting rolling temperature is 850 to 1000°C, preferably 850 to 950°C, and the finishing rolling temperature is 650 to 800°C, preferably 680 to 750°C.
[0047] In order to more effectively control the grain size and growth rate, in a preferred embodiment, in step S1, the deformation amount of the first cold rolling is 80-90%; and / or, the temperature of the recrystallization treatment is 920-950°C, and the time is 1-10 min.
[0048] For the purpose of further effectively regulating the size and surface distribution density of the precipitated phase, in a preferred embodiment, in step S2, the deformation amount of the second cold rolling is 60-80%; and / or, the temperature of the aging treatment is 450-550°C, and the time is 4-8h.
[0049] In a preferred embodiment, in step S3, the deformation amount of the third cold rolling is 40-50%, and / or the temperature of the stress relief treatment is 300-400°C and the time is 60-90s. Under the above conditions, the cold deformation residual stress can be more fully eliminated, which is more conducive to improving the strip shape.
[0050] In a preferred embodiment, in step S1, the average grain diameter of the strip is 40-90 μm. The inventors have found through a large number of experiments that when the alloy grain size is between 40-90 μm, the grain boundary mobility can be further reduced, thereby being more conducive to improving the alloy's stress relaxation resistance.
[0051] In a preferred embodiment, in step S2, the length of the precipitated phase in the strip is 200-600 nm, and the phase distribution density is 500-1000 / μm. 2 The inventors have found through a large number of experiments that when a rod-shaped precipitate phase with a length of 200-600 nm is formed in the matrix, its distribution density ρ is between 500-1000 / μm 2 When the alloy is subjected to high stress, the expansion of dislocations can be more effectively hindered, thereby further improving the alloy's resistance to stress relaxation.
[0052] In a preferred embodiment, the average grain diameter of the CuCr-X alloy is 30-60 μm. The inventors obtained the CuCr-X alloy under the above conditions by optimizing various test parameters. The CuCr-X alloy has good strength, electrical conductivity and stress relaxation resistance.
[0053] In another typical embodiment of the present invention, the application of the above-mentioned CuCr-X alloy in automobile, aviation and aerospace fields is also provided. As mentioned above, the present invention adds Sn, Mg and Ti alloying elements on the basis of CuCr alloy, and the radius difference of Sn, Mg, Ti and Cu atoms is large, and being scattered in the matrix will produce obvious hindering effect on the movement of dislocation, and can effectively improve the strength and stress relaxation resistance of the alloy. Wherein Sn and Mg elements are solid-dissolved in the matrix, and matrix vacancies can be effectively eliminated, and the creep of atoms at high temperature can be reduced, so as to be conducive to improving the stress relaxation resistance of the alloy. In addition, the addition of specific content Sn, Mg and Ti has little effect on the electrical conductivity of the alloy. The alloy of the present invention can take into account strength, electrical conductivity and stress relaxation resistance, and is used in automobile, aviation and aerospace fields, especially when it can be used as a connector material, it can meet the use requirements of modern high-end connectors in high temperature and high vibration environments, and ensure the reliable operation of electronic devices.
[0054] Typically, but not limiting, the composition of the CuCr-X alloy is such that Cr / (Mg+Ti) is 3, 4, 5, 6 or a range consisting of any two of these values.
[0055] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0056] Example 1
[0057] The composition of CuCr-X alloy is shown in Table 1.
[0058] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 850℃, final rolling temperature is 650℃), to obtain a hot-rolled slab with a thickness of 15mm. The hot-rolled slab is subjected to 95% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 900℃ and a holding time of 10min to obtain a strip with a thickness of 0.8mm and an average grain diameter of 43.2μm;
[0059] Step S2, the recrystallized strip is subjected to 60% cold rolling deformation to obtain a strip with a thickness of 0.32 mm, and then the strip is subjected to precipitation phase regulation by an overaging process. The overaging treatment temperature is 450°C, and the holding time is 8 hours. The length L of the rod-shaped precipitation phase formed in the obtained strip is 215 nm, and the distribution density ρ of the precipitation phase is 521 / μm 2 ;
[0060] Step S3, cold rolling the plate with a thickness of 0.154 mm by 42% to obtain a strip with a thickness of 0.09 mm, and then performing stress relief treatment at a stress relief treatment temperature of 300°C and a holding time of 120s to obtain a CuCr-X alloy with an average grain diameter of 33.2 μm.
[0061] The grain structure diagram of CuCr-X alloy is shown in Figure 1 .
[0062] Example 2
[0063] The composition of CuCr-X alloy is shown in Table 1.
[0064] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 850℃, final rolling temperature is 680℃), and a hot-rolled slab with a thickness of 15mm is obtained. The hot-rolled slab is subjected to 90% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 910℃ and a holding time of 8min to obtain a strip with a thickness of 1.5mm and an average grain diameter of 56.5μm;
[0065] Step S2, the recrystallized strip is subjected to 60% cold rolling deformation, and then the strip is subjected to precipitate phase regulation by an overaging process. The overaging treatment temperature is 480°C, and the holding time is 6h. The length L of the rod-shaped precipitate phase formed in the obtained strip is 278nm, and the precipitate phase distribution density ρ is 546 / μm 2 ;
[0066] Step S3, continue to perform 50% cold rolling deformation on the plate and strip, and then perform stress relief treatment. The stress relief treatment temperature is 350° C. and the holding time is 100 s, to obtain a CuCr-X alloy with an average grain diameter of 36.5 μm.
[0067] Example 3
[0068] The composition of CuCr-X alloy is shown in Table 1.
[0069] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 880℃, final rolling temperature is 700℃), and a hot-rolled slab with a thickness of 12mm is obtained. The hot-rolled slab is subjected to 90% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 930℃ and a holding time of 8min to obtain a strip with an average grain diameter of 52.6μm;
[0070] Step S2, the recrystallized strip is subjected to 65% cold rolling deformation, and then the strip is subjected to precipitate phase regulation by an overaging process. The overaging treatment temperature is 500°C, and the holding time is 5h. The length L of the rod-shaped precipitate phase formed in the obtained strip is 316nm, and the precipitate phase distribution density ρ is 680 / μm 2 ;
[0071] Step S3, continue to perform 40% cold rolling deformation on the plate and strip, and then perform stress relief treatment. The stress relief treatment temperature is 340° C. and the holding time is 90 s, to obtain a CuCr-X alloy with an average grain diameter of 42.3 μm.
[0072] Example 4
[0073] The only difference from Example 1 is:
[0074] The alloy compositions are different, see Table 1 for details.
[0075] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 900℃, final rolling temperature is 720℃), to obtain a hot-rolled slab with a thickness of 12mm. The hot-rolled slab is subjected to 85% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 940℃ and a holding time of 4min to obtain a strip with an average grain diameter of 69.2μm;
[0076] Step S2, the recrystallized strip is subjected to 70% cold rolling deformation, and then the strip is subjected to precipitate phase regulation by an over-aging process. The over-aging treatment temperature is 550°C, and the holding time is 4h. The length L of the rod-shaped precipitate phase formed in the obtained strip is 425nm, and the precipitate phase distribution density ρ is 780 / μm 2 ;
[0077] Step S3, cold rolling the plate and strip by 40%, and then performing stress relief treatment, the stress relief treatment temperature is 400°C, and the holding time is 70s, to obtain a CuCr-X alloy with an average grain diameter of 52.8μm.
[0078] Example 5
[0079] The only difference from Example 1 is:
[0080] The alloy compositions are different, see Table 1 for details.
[0081] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 1000℃, final rolling temperature is 800℃), to obtain a hot-rolled slab with a thickness of 8mm. The hot-rolled slab is subjected to 75% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 960℃ and a holding time of 1min to obtain a strip with an average grain diameter of 88μm;
[0082] Step S2, the recrystallized strip is subjected to 85% cold rolling deformation, and then the strip is subjected to precipitate phase regulation by an overaging process. The overaging treatment temperature is 600°C, and the holding time is 2h. The length L of the rod-shaped precipitate phase formed in the obtained strip is 568nm, and the precipitate phase distribution density ρ is 960 / μm 2 ;
[0083] Step S3, cold rolling the plate and strip by 40%, and then performing stress relief treatment at a stress relief treatment temperature of 450°C and a holding time of 30s to obtain a CuCr-X alloy with an average grain diameter of 58 μm.
[0084] Examples 6 to 10
[0085] The only difference from Example 4 is that:
[0086] The alloy compositions are different, see Table 1 for details.
[0087] Comparative Example 1
[0088] The only difference from Example 4 is that:
[0089] The alloy composition does not contain Sn, Ti, and Mg;
[0090] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 850℃, final rolling temperature is 670℃), and a hot-rolled slab with a thickness of 15mm is obtained. The hot-rolled slab is subjected to 95% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 910℃ and a holding time of 8min to obtain a strip with an average grain diameter of 113μm;
[0091] Step S2, the recrystallized strip is subjected to 60% cold rolling deformation, and then the strip is subjected to aging process to regulate the precipitation phase. The aging treatment temperature is 480°C, the holding time is 6h, and the main precipitated phase formed is spherical, the average grain diameter is about 936nm, and the phase distribution density ρ is 350 / μm 2 ;
[0092] Step S3, cold rolling the plate and strip by 40% to obtain a strip, and then performing stress relief treatment at a stress relief treatment temperature of 350° C. for a holding time of 100 s to obtain a CuCr-X alloy having an average grain diameter of 96 μm.
[0093] Comparative Example 2
[0094] The only difference from Example 4 is that:
[0095] The alloy composition does not contain Ti and Mg.
[0096] Step S1, according to the composition ratio of CuCr-X alloy, batching, melting and casting, hot rolling (2 passes, starting rolling temperature is 1000℃, final rolling temperature is 780℃), to obtain a hot-rolled slab with a thickness of 12mm. The hot-rolled slab is subjected to 85% cold rolling deformation, and then recrystallization treatment is performed at a treatment temperature of 960℃ and a holding time of 20min to obtain a strip with an average grain diameter of 158μm;
[0097] Step S2, the recrystallized strip is subjected to 72% cold rolling deformation, and then the precipitate phase of the strip is regulated by an over-aging process. The over-aging treatment temperature is 550°C, and the holding time is 3h. The main precipitate phase formed in the obtained strip is spherical, with an average grain diameter of about 1565nm and a precipitate distribution density ρ of 294 / μm 2 ;
[0098] Step S3, the plate strip is subjected to 40% cold rolling deformation, and then subjected to stress relief treatment, the stress relief treatment temperature is 420°C, and the holding time is 60s, to obtain a CuCr-X alloy with an average grain diameter of 132μm. The grain structure diagram of the CuCr-X alloy is shown in Figure 2 .
[0099] Comparative Examples 3 to 6
[0100] The only difference from Example 4 is that:
[0101] The alloy compositions are different, see Table 1 for details.
[0102] Comparative Example 7
[0103] The only difference from Example 4 is that:
[0104] In step S1, the starting temperature of hot rolling is 800°C and the finishing temperature is 630°C.
[0105] Comparative Example 8
[0106] The only difference from Example 4 is that:
[0107] In step S1, the starting temperature of hot rolling is 1020°C and the finishing temperature is 840°C.
[0108] Comparative Example 9
[0109] The only difference from Example 4 is that:
[0110] Step S1, subjecting the hot-rolled slab to 99% cold rolling deformation, the recrystallization treatment temperature is 980°C, and the holding time is 0.5min.
[0111] Comparative Example 10
[0112] The only difference from Example 4 is that:
[0113] Step S1, subjecting the hot-rolled slab to 70% cold rolling deformation, the recrystallization treatment temperature is 880°C, and the holding time is 15 minutes.
[0114] Comparative Example 11
[0115] The only difference from Example 4 is that:
[0116] Step S2, subjecting the recrystallized strip to 50% cold rolling deformation, the aging treatment temperature is 420°C, and the holding time is 10 hours.
[0117] Comparative Example 12
[0118] The only difference from Example 4 is that:
[0119] Step S2, subjecting the recrystallized strip to 90% cold rolling deformation, the aging treatment temperature is 650°C, and the holding time is 1h.
[0120] Comparative Example 13
[0121] The only difference from Example 4 is that:
[0122] Step S3, the over-aging treated sheet and strip are subjected to 65% cold rolling deformation, and then subjected to stress relief treatment, the stress relief treatment temperature is 280° C., and the holding time is 200 s.
[0123] Comparative Example 14
[0124] The only difference from Example 4 is that:
[0125] Step S3, the over-aging strip is subjected to 35% cold rolling deformation, and then subjected to stress relief treatment, the stress relief treatment temperature is 480° C., and the holding time is 15 s.
[0126] The test results of the average grain diameter of the CuCr-X alloy strips prepared in the above embodiments and comparative examples, the length and phase distribution density of the precipitated phase in the plate and strip, and the average grain diameter of the CuCr-X alloy are shown in Table 2, and the test results of tensile strength, elongation, hardness, conductivity, and stress relaxation rate are shown in Table 3.
[0127] Test method:
[0128] Grain size, precipitated phase length, phase distribution density: refer to the standard GB / T 6394 "Method for determination of average grain size of metals" for grain size analysis.
[0129] Tensile strength, elongation, Vickers hardness: Tested in accordance with standard GB / T 228.1 "Tensile test of metallic materials Part 1: Room temperature test method".
[0130] Conductivity: Tested in accordance with standard GB T 32791 “Eddy current test method for electrical conductivity of copper and copper alloys”.
[0131] Stress relaxation rate: Tested in accordance with standard GB T10120 “Test method for tensile stress relaxation of metallic materials”.
[0132] Table 1
[0133]
[0134] Table 2
[0135]
[0136] Table 3
[0137]
[0138] As can be seen from the above, compared with the comparative example, the present invention optimizes the alloy composition, adds specific contents of Sn, Mg, and Ti alloying elements on the basis of CuCr alloy, and Sn, Mg, Ti and Cu cooperate with each other, which can effectively eliminate matrix vacancies and reduce the creep of atoms at high temperatures, thereby helping to improve the strength and stress relaxation resistance of the alloy. Moreover, the addition of specific contents of Sn, Mg, and Ti has little effect on the electrical conductivity of the alloy. The alloy of the present invention has good strength, electrical conductivity, and stress relaxation resistance. When used in the automotive, aviation, and aerospace fields, it can meet the use requirements of high-end connectors in high temperature and high vibration environments, and ensure the reliable operation of electronic devices.
[0139] In addition, it can be seen that when the process parameters are within the preferred range of the present invention, the strength, electrical conductivity and stress relaxation resistance of the CuCr alloy are better matched.
[0140] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A CuCr-X alloy, characterized in that: The composition of the CuCr-X alloy includes, by weight percentage, 0.85-1.25% Cr, 0.05-0.4% Sn, 0.02-0.4% Mg, 0.02-0.2% Ti, and the balance is Cu and unavoidable impurity elements, wherein Cr / (Mg+Ti)=3-6, and the total weight percentage of Sn and Mg is 0.2-0.5%. The preparation method of the CuCr-X alloy comprises the following steps: Step S1, according to the composition ratio of the CuCr-X alloy, batching, melting and casting, hot rolling are carried out in sequence to obtain a hot-rolled slab; the hot-rolled slab is subjected to a first cold rolling and recrystallization treatment in sequence to obtain a strip; Step S2, subjecting the strip to a second cold rolling and an over-aging treatment in sequence to obtain a plate strip; Step S3, performing a third cold rolling and a stress relief treatment on the plate strip in sequence to obtain the CuCr-X alloy; In the step S1, the temperature of the recrystallization treatment is 930-950°C, and the average grain diameter of the strip is 40-90 μm.
2. The CuCr-X alloy according to claim 1, characterized in that The composition of the CuCr-X alloy includes, by weight percentage, 0.85-1.25% Cr, 0.15-0.28% Sn, 0.11-0.2% Mg, 0.05-0.15% Ti, and the balance is Cu and unavoidable impurity elements, wherein Cr / (Mg+Ti)=4-5.
3. The CuCr-X alloy according to claim 1 or 2, characterized in that: The composition of the CuCr-X alloy is: The total weight percentage of Sn and Mg is 0.3~0.4%.
4. The CuCr-X alloy according to claim 1 or 2, characterized in that: The CuCr-X alloy has a tensile strength of 580-650 MPa, a conductivity of 75-82% IACS, and a stress relaxation rate of ≤8% after being kept at 150° C. for 1000 hours; and / or, The elongation of the CuCr-X alloy is 3-8%.
5. The CuCr-X alloy according to claim 1 or 2, characterized in that: In step S1, the deformation amount of the first cold rolling is 75-95%; and / or, the time of the recrystallization treatment is 1-10 minutes; and / or, In step S2, the deformation amount of the second cold rolling is 55-85%; and / or, the temperature of the over-aging treatment is 450-600°C and the time is 2-8h; and / or, In step S3, the deformation amount of the third cold rolling is 40-60%; and / or, the temperature of the stress relief treatment is 300-450° C., and the time is 30-120 seconds; and / or, The thickness of the CuCr-X alloy is 0.05-0.5 mm.
6. The CuCr-X alloy according to claim 1 or 2, characterized in that: In the step S1, The hot rolling is performed in 1 to 2 passes, the starting rolling temperature is 850 to 1000°C, and the final rolling temperature is 650 to 800°C.
7. The CuCr-X alloy according to claim 1 or 2, characterized in that: In the step S1, The deformation amount of the first cold rolling is 80-90%; and / or, The recrystallization treatment time is 1 to 10 minutes.
8. The CuCr-X alloy according to claim 1 or 2, characterized in that: In the step S2, The deformation amount of the second cold rolling is 60-80%; and / or, The temperature of the over-aging treatment is 450-550° C. and the time is 4-8 hours.
9. The CuCr-X alloy according to claim 1 or 2, characterized in that: In the step S3, The deformation amount of the third cold rolling is 40-50%; and / or, The stress relief treatment is performed at a temperature of 300-400° C. and for a time of 60-90 seconds.
10. The CuCr-X alloy according to claim 1 or 2, characterized in that: In step S2, the length of the precipitated phase in the strip is 200-600 nm, and the phase distribution density is 500-1000 / μm. 2 .
11. The CuCr-X alloy according to claim 1 or 2, characterized in that: The average grain diameter of the CuCr-X alloy is 30-60 μm.
12. Application of the CuCr-X alloy according to claim 1 or 2 in the fields of automobile, aviation and aerospace.
Citation Information
Patent Citations
Copper alloy strips for electrical and electronic parts
JP6283048B2
High-conductivity heat-resistant copper alloy for ultrathin vapor chamber and preparation method of high-conductivity heat-resistant copper alloy
CN116219224A
High-performance copper-chromium alloy and preparation method thereof
CN117821796A
Cu-Cr-BASED COPPER ALLOY FOR ELECTRONIC MATERIAL
JP2008081762A